Avaliação da aprendizagem como ato reflexivo no ensino da matemática nas turmas de 9º ano da Escola Municipal Paulo Rodrigues dos Santos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The main objective of this research was to understand how the evaluation of learning is carried out through the contents of mathematics worked in the 9th grade classes, their difficulties and their causes after the process in the context of the Paulo Rodrigues dos Santos Municipal School in the municipality of Santarém, in the west of Pará. The methodology was based on the quantitative-qualitative approach, starting from the bibliographic studies as a means of being able to understand the relation of the systematization theory of evaluation in the teaching and learning process and the field research, through observations and the application of a questionnaire, which can make a more proximal relationship between the theory and practice of school everyday in the 9th grade classes. Therefore, the evaluation in the teaching of mathematics when exercised with seriousness, seeks to conduct teaching and learning parallel to the competences and content skills. However, it is concluded that the mathematics teachers of the classes surveyed have demonstrated interest, responsibility, flexibility in teaching and its evaluation process.
Keywords: Avaliação; Matemática; Ensino; Aprendizagem; Conteúdos; CNPQ:: CIÊNCIAS EXATAS E DA TERRA